2011
DOI: 10.4142/jvs.2011.12.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with bacteriological cure, new infection, and incidence of clinical mastitis after dry cow therapy with three different antibiotics

Abstract: Factors affecting bacteriological cure rates (BCR) and new intramammary infections (IMI) during the dry period as well as clinical mastitis (CM) during early lactation were investigated in 414 German Holstein dairy cows receiving dry cow therapy. Cows were treated with either benethamine benzylpenicillin (300,000 IU), penethamate hydriodide (100,000 IU), and framycetin sulphate (100 mg, n = 136), or cefquinome (150 mg, n = 135), or benzathine cloxacillin (1,280 mg, n = 143). Overall BCR, IMI, and CM at parturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
22
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 20 publications
11
22
3
1
Order By: Relevance
“…Antimicrobials are routinely used for the treatment of bovine mastitis although there is a considerable variation in the clinical outcome for cows infected with S . aureus [ 16 , 17 , 18 ]. Therapeutic failure of antibiotics may be due to the ability of the bacteria to form a well-structured biofilm [ 1 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobials are routinely used for the treatment of bovine mastitis although there is a considerable variation in the clinical outcome for cows infected with S . aureus [ 16 , 17 , 18 ]. Therapeutic failure of antibiotics may be due to the ability of the bacteria to form a well-structured biofilm [ 1 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further Scherpenzeel et al (2014) reported 1.7 times higher incidence of clinical mastitis at quarter level in cows dried off without antibiotic than control. Previous studies reported lower incidence of clinical mastitis (3-6% at quarter level and 10.1-14.2% at cow level) during early lactation in dairy cows treated with DCT (Godden et al, 2003;Gundelach et al, 2011;Arruda et al, 2013;Johnson et al, 2016). Further, meta-analysis study on dry cow therapy indicated that quarters infused with DCT have higher cure risk and lower new IMI risk over the dry period than untreated quarters (Halasa et al, 2009).…”
Section: Results and Discussion Incidence Of Clinical Mastitismentioning
confidence: 96%
“…increase in diameter of the teat canal, diminished function of the teat canal sphincter), and reduced resistance with increasing age are possible reasons for an increased risk of infection. (19) In this study, there was no significant difference in skin scores when treatment time was analyzed, suggesting low or no toxicity of the product used in pre-and post-milking, when comparing fortnight results in each one. According to this, we can state that the hydroalcoholic extract of Schinus terebintifolius Raddi can be used as an antiseptic in pre-and post-milking because it showed no toxicity when compared to the conventional treatment with commercial iodine.…”
Section: Resultsmentioning
confidence: 98%
“…The duration of infections in cows is an important point that should be considered because the faster mastitis cases are eliminated the greater are the chances of success of control programs. (18) Gundelach (19) reported that Staphylococcus spp. coagulase negative caused approximately 85% of new intramammary infections.…”
Section: Resultsmentioning
confidence: 99%